Fun Camp: Mewujudkan Semangat Mappatuo dan Mappasilasa Wija to Luwu (Fun Camp IPMIL) Sebagai Ruang Penguatan Nilai Budaya - Muhammad Janwar; Suhardianto Suhardianto; Deddy Yusuf (Yayasan Habiburrahman Jamalu Bina Ummat, 2026)
This Community Service (PKM) activity aims to strengthen the local cultural values ​​of Luwu, especially the values ​​of mappatuo and mappasilasa, through the FUN CAMP activity implemented by the Indonesian Student Association of Luwu (IPMIL) Unimerz. Globalization and technological developments have had an impact on weakening the internalization of local cultural values ​​​​among the younger generation. Therefore, an educational space that is participatory, recreational, and based on direct experience is needed. The method of implementing the activity uses a participatory approach through educational games, cultural discussions, reflection on values, and outdoor activities. The results of the activity showed an increase in participants' understanding of Luwu cultural values, an increased sense of togetherness, solidarity, and commitment to implementing the values ​​​​of mappatuo and mappasilasa in daily life and organizations. This activity makes a positive contribution to the character development of the younger generation of Wija to Luwu and strengthens the role of IPMIL as an agent of cultural preservation.